Bronze Age non-elite mobility in Denmark examined through a new human-based bioavailable strontium isotope range - Karin Margarita Frei; Malene Refshauge Beck; Pernille Pantmann; Niels Algreen Møller; Morten Søvsø; Robert Frei (PLoS ONE, 2026)
Strontium isotope analysis is now a key method for investigating ancient human mobility, leading to a rapid expansion of available ⁸⁷Sr/⁸⁶Sr datasets. Owing to the relatively homogeneous surface geological conditions across present-day Denmark (excluding Bornholm) and the growing number of regional datasets, it is now possible to construct statistically defined ranges of bioavailable strontium directly from archaeological human data. In this study, we compile 513 published strontium isotope values from tooth enamel and pars petrosa of individuals recovered from archaeological sites across present-day Denmark and add 115 new values. Using the Median Absolute Deviation (MAD) method to identify outliers in this comprehensive and diachronic database of 628 human ⁸⁷Sr/⁸⁶Sr ratios, we define the first statistically constrained, human-based range of bioavailable strontium isotope values for Denmark to ⁸⁷Sr/⁸⁶Sr = 0.7089–0.7117. We interpret this range as representing typical bioavailable strontium signatures in prehistoric Denmark. We then apply it, for the first time, as one of the reference frameworks for investigating the mobility of non-elite individuals from the Nordic Bronze Age in present-day Denmark. In total, we conducted 34 strontium isotope analyses on individuals from two sites: fourteen analyses from six inhumations at Kalvehavegård on Funen, and twenty analyses from cremated individuals at Sølager on Zealand. We compare the individuals’ strontium isotope values both to established baselines relevant for past mobility studies and to the new human-based range defined in this study. The results indicate that mobility during the Nordic Bronze Age was not restricted to elite social groups but also encompassed some non-elite individuals, offering new insights into social dynamics during this formative period of European prehistory. Moreover, the new strontium dataset presented here represents the first accessible, country-wide compilation of human-derived Sr data for Denmark, providing a robust platform for future comparative studies and mobility research in the region.